The Measurement of Reinvested Earnings in the Balance of Payments - Bame, Jack (IMF Working Papers; Working Paper, 1995)
This paper notes that, for the first time, the concept and treatment of reinvested earnings in the Fund's Balance of Payments Manual and the 1993 System of National Accounts are fully harmonized. The paper presents the conceptual basis for the measurement of reinvested earnings and illustrative examples as to recording, from the Fund's Balance of Payments Compilation Guide and Balance of Payments Textbook. Highlighted are the recommended time of recording of reinvested earnings, the calculation of earnings on a current operating basis, and the calculation of depreciation at replacement cost, notwithstanding possible practical difficulties in implementation.